اسد محمد خان کے افسانے "باسودے کی مریم "کاتجزیاتی مطالعہ - Shahabuddin; Dr Anwar Ali (Khayaban - خیابان, 2022)
ABSTRACT: Asad Muhammad Khan is a distinguished name in the world of literature. His Short story ‘Basauday ki Maryam’ has garnered great applause in the literary circles. This short story is the main source of reference for his fame in the field of art. This short story ‘Basauday ki Maryam’ is a magnum opus of the writer, which has earned him everlasting fame and distinction. Ahmad Nadim Qasmi has said that if the short story vanished away, still this story ‘Basauday ki Maryam’ will live for ever. Dr. Anwar Ahmad has termed this story as a pleasant wave in the field of eulogizing literature of urdu language and Mubeen Mirza has termed it a symbol of Indian Islamic Culture. Maryam who is a poor and uneducated Mevati woman, but her heart is set on fire by the love of Holy Prophet (S.A.W.W) and she has only one aim in her life to go to Makkah and Madina to pay her tribute to the Holy Prophet (S.A.W.W).